If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + 6 = 36 Reorder the terms: 6 + 6n = 36 Solving 6 + 6n = 36 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6n = 36 + -6 Combine like terms: 6 + -6 = 0 0 + 6n = 36 + -6 6n = 36 + -6 Combine like terms: 36 + -6 = 30 6n = 30 Divide each side by '6'. n = 5 Simplifying n = 5
| 5+2x-4x+6= | | 5(1-2w)+8w=1 | | 6x-1=2x+10 | | (n-3)*7=42 | | (n-3)*3=27 | | y-2y+5= | | 14=x+5 | | x-4x+3= | | (n+1)*5=15 | | 3x+10=5x-1 | | n-13=25 | | n*2=22 | | -x+2-x-2= | | n-7=5 | | 8y-1=2y+23 | | n+25=35 | | 5x-2=12x-79 | | 5x+2y+3+y= | | 5=x-7 | | 7m+1=2m+7 | | n-6=18 | | n*6=54 | | n+29=49 | | -2x-3x-2-3= | | -4+5x+12= | | 3-8x+5= | | -6.9=-2.76-4.6x | | 4x-7x+4= | | -2x+5x= | | -2x-3x= | | y+3+4y= | | 4x-5x= |